O letramento estatístico: uma ponte entre a aprendizagem acadêmica e a prática: Statistical literacy: a bridge between academic learning and practice - Tanus , Sarah; Hanai-Yoshida, Valquíria Miwa; Profeta, Rogério Augusto (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
Statistical education is becoming increasingly relevant in the digital age, marked by data-driven decision-making. However, it still faces persistent challenges. Research conducted by the Program for the International Assessment of Adult Competencies (PIAAC) and the Program for International Student Assessment (PISA) highlights the difficulties many adults face in interpreting statistical data. This article on statistical education in higher education is based on a survey that analyzed the perceptions of professionals from the Sorocaba Metropolitan Region about the implementation and use of statistical knowledge in the professional environment. The study aimed to identify the critical points for implementing and disseminating statistical techniques and thinking in companies, exploring the gap between academic training in statistics and its practical application. The quantitative methodology was based on a structured questionnaire completed by 410 professionals from the region, and the data analysis categorized the companies, represented by the professionals' responses, into three levels of statistical proficiency: beginner, intermediate, and advanced. The results indicate that the main challenges to implementing statistics in companies include the need for data culture and limited statistical competence. It is concluded that the development of statistical literacy can overcome the barriers between available statistical tools and their application in organizations. This study aligns with the perspective of promoting conscious statistical education and is focused on ways to mobilize knowledge in the service of people and their projects.